Relações de amizade em meninos com transtorno de déficit de atenção /hiperatividade (TDAH) - Soraya da Silva Sena (2009)
The ADHD is a neurobehavioral syndrome characterized by persistent pattern of inattention and / or hyperactivity-impulsivity. The international literature reports that individuals with ADHD have difficulties in relationships with peers due to the impact of symptoms on interpersonal relationships. In this study 39 children were interviewed from seven to nine years of age and their parents or guardians. This sample, 18 boys joined the Clinical Group (children with ADHD) and 21 joined the Group Typical (children without ADHD). Investigated the relationship of friendship for children through two semi-structured interviews on friendship, one for children and another for their parents. Also, the kids responded the Friendship Quality Scale, which seeks information on the best friend of the interviewee. All boys in the sample indicated the existence of at least one friend. The response category of "Play" was the most frequent question about the conditions of friendship in both groups. There was disagreement between the reports of parents and children on these friendships. In Clinical Group, 17% of parents denied the existence of the child's friend. In Group Typical, all the boys reported reciprocity of friendship. However, in the Clinical Group, 17% of boys reported no reciprocity of friendship. We discuss the possible change in the perception of interpersonal relationships between members of the Clinical Group. Note the difference in the concept of friendship between adults and children as a hypothesis for explaining the difference in reporting on the friendship between parents and children interviewed. Indicates the need for future research is expanding the number of participants. It is suggested, too, which made studies of adolescent and adult patientswith ADHD of both sexes. This study is expected to have contributed to the knowledge of friendly relations of individuals with ADHD.